Perception of double‐stranded RNA in plant antiviral immunity. (3rd April 2019) - Niehl, Annette; Heinlein, Manfred
Summary: RNA silencing and antiviral pattern‐triggered immunity (PTI) both rely on recognition of double‐stranded (ds)RNAs as defence‐inducing signals. While dsRNA recognition by dicer‐like proteins during antiviral RNA silencing is thoroughly investigated, the molecular mechanisms involved in dsRNA perception leading to antiviral PTI are just about to be untangled. Parallels to antimicrobial PTI thereby only partially facilitate our view on antiviral PTI. PTI against microbial pathogens involves plasma membrane bound receptors; however, dsRNAs produced during virus infection occur intracellularly. Hence, how dsRNA may be perceived during this immune response is still an open question. In this short review, we describe recent discoveries in PTI signalling upon sensing of microbial patterns and endogenous 'danger' molecules with emphasis on immune signalling‐associated subcellular trafficking processes in plants. Based on these studies, we develop different scenarios how dsRNAs could be sensed during antiviral PTI.